Analysis of time-dependent changes in Bitemarks on Styrofoam sheets - Djeapragassam Parimala; Mariappan Jonathan Daniel; Subramanian Vasudevan Srinivasan; Jimsha Vannathan Kumaran (Wolters Kluwer Medknow Publications, 2015)
Context: The scope of Bitemarks in forensic dentistry is widening as they help the forensic expert in identifying the perpetuator in medicolegal cases. The greatest challenge in Bitemarks analysis is the time-dependent changes produced in Bitemark patterns on various substrates at the scene of the crime. Aims: To analyze the time-dependent changes in Bitemarks on Styrofoam sheets. Settings and Design: Single centered prospective study. Materials and Methods: Twenty-five subjects were randomly chosen, and dental casts prepared. Then test bites were registered on Styrofoam sheets, overlays prepared from these test bites on subsequent days (day 1, 2, 3, 4) and checked for matching accuracy. Statistical Analysis Used: The data were analyzed using Kruskal-Wallis ANOVA to compare the overlays from dental stone cast with test bites on Styrofoam sheets on subsequent days. Results: The P value was found to be 1 which is statistically not significant implying that there were no significant time-dependent changes in the pattern of Bitemarks. Conclusions: There were no time-dependent changes in the pattern of Bitemarks on Styrofoam sheets hence they serve as better materials than Bitemarks on human skin or food substrates obtained from the scene of the crime.